Fake news and its impact on national cohesion: the Nigerian story - Silas Udenze (Center for Humanities and Innovation Studies, 2021)
This discussion paper explores fake news and its impact on national cohesion: the Nigerian perspective. Recently, fake news has become a global phenomenon and impacts nations' economic and socio-political activities. The current discussion paper utilizes secondary sources to buttress the effects of fake news on Nigeria's national cohesion. The paper opined that fake news intentionally fabricated and disseminated information to deceive and mislead others into believing falsehoods. Further, the study discovered that some of the adverse effects of fake news include ethno-religious crisis, electoral violence, and economic instability, among others. Also, it identified the causes of fake news as the mistrust of the ruling class by the masses, social media and affordable data, capitalist motives, late release of information by agencies of government, inadequate capacities of media outlets to verify and release authentic information etc. As a result of fake news, it is recommended that: There is a need always to check multiple sources to confirm the authenticity information before dissemination. We are encouraged to use verification tools and also check the metadata of the information. We should endeavor to be media literate; think before disseminating any information. However, fake news's menace may be impossible to eradicate, but its negative implications can be reduced or managed if we are committed to the preceding statement.